Enhancing Problem-Solving Skills and Spirit of Mutual Cooperation in Mathematics Learning through Teaching at the Right Level Approach - Farid Bashirudin Yusuf; Fery Muhamad Firdaus; Kadir (Universitas Pendidikan Ganesha, 2024)
The importance of learning mathematics is inversely proportional to the fact that using conventional learning methods causes low problem-solving abilities and the spirit of cooperation among students. Another problem encountered was that students still needed help solving problems related to flat figures, and only a few students had a spirit of cooperation during group work. This research aims to identify and analyze the impact of implementing the TaRL approach in improving students' problem-solving skills, the spirit of cooperation, and social interaction in mathematics learning. This research is a qualitative descriptive study. This research was conducted on 27 fourth-grade elementary school students. Data collection techniques in this research used research instruments in the form of interviews, observation, questionnaires, and documentation. This data analysis technique uses the Miles and Huberman (1994) method. The research results show a significant increase in mathematics learning. Applying the TaRL approach has resulted in a significant increase in first and second-cycle scores, especially at the intermediate knowledge level, which increased from 68.57% to 72.33%, and at the high level, which increased from 73.00% to 76.00%. In addition, there was a significant increase in the students' spirit of cooperation, with the